A new perspective on prostate cancer treatment: the interplay between cellular senescence and treatment resistance - Xu, Meng-Yao; Xia, Zhi-Yu; Sun, Jian-Xuan; Liu, Chen-Qian; An, Ye; Xu, Jin-Zhou; Zhang, Si-Han; Zhong, Xing-Yu; Zeng, Na; Ma, Si-Yang; He, Hao-Dong; Wang, Shao-Gang; et al. (Frontiers in Immunology, 2024)
The emergence of resistance to prostate cancer (PCa) treatment, particularly to androgen deprivation therapy (ADT), has posed a significant challenge in the field of PCa management. Among the therapeutic options for PCa, radiotherapy, chemotherapy, and hormone therapy are commonly used modalities. However, these therapeutic approaches, while inducing apoptosis in tumor cells, may also trigger stressinduced premature senescence (SIPS). Cellular senescence, an entropy-driven transition from an ordered to a disordered state, ultimately leading to cell growth arrest, exhibits a dual role in PCa treatment. On one hand, senescent tumor cells may withdraw from the cell cycle, thereby reducing tumor growth rate and exerting a positive effect on treatment. On the other hand, senescent tumor cells may secrete a plethora of cytokines, growth factors and proteases that can affect neighboring tumor cells, thereby exerting a negative impact on treatment. This review explores how radiotherapy, chemotherapy, and hormone therapy trigger SIPS and the nuanced impact of senescent tumor cells on PCa treatment. Additionally, we aim to identify novel therapeutic strategies to overcome resistance in PCa treatment, thereby enhancing patient outcomes.